Peran Virtual Experiential Marketing dan Brand Trust terhadap Brand Loyalty: Peran Virtual Experiential Marketing dan Brand Trust terhadap Brand Loyalty - khoirunissa, Alvi diani; Rufaidah, Popy (Jurnal Sosioteknologi, 2024)
The purpose of this study is to analyze the role of virtual experiential marketing and brand trust in brand loyalty among virtual try-on cosmetic filter users in Indonesia. An online tool made using Google Forms and shared on social media was used to perform the research. SEM-PLS was the statistical method employed to examine 287 convenience sample data. The results showed that virtual experiential marketing has a positive impact on brand loyalty, and brand trust has a positive impact on brand loyalty. The study recommends the most effective indicators of virtual experiential marketing, identifying external factors that influence a cosmetics brand's strategy in Indonesia in forming trust and loyalty, and using the virtual try-on filter feature to build trust through positive virtual experiences.